Organic farming, a viable and feasible component of the Romanian agriculture - Anda-Irina Angelescu; Ioan Niculae Alecu; Adriana Badea (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
Taking into account the fact that organic farming is not a miracle, but a tangible reality of our days, a trend with more and more followers within the producers and consumers, this paper is included within those trying to demonstrate once more that for Romania also, the organic farming is a viable alternative to the traditional farming that leads in time to the degradation of soil and water resources, to air pollution, degradation of population heath etc. By using as working method the direct observation without intervention and consulting specialized reference sources, we have tried to select the most important definitions for the Romanian organic farming. We have also specified the objectives and principles of the organic farming and we have made a selection of the most important legal regulations on which the environment-friendly production is based, both at Community level and at national level. The analysis of the organic farming in Romania also showed that a process of institutional strengthening and development is currently undergoing for the organic farming, as in all the other countries, and the Ministry of Agriculture and Rural Development, by its actions, puts the organic farming in the centre of the development of the Romanian agriculture. As such, the evolution of this sector from one year to another was dynamic, with a steady pace growth of the eco-cultivated areas and of the number of animals resulted from organic livestock breeding. The analysis performed entitles us to consider that the organic farming is an inadequately capitalized opportunity for Romania that could place the country as a front-runner on the European market.
Keywords: 330; Organic farming; conventional farming; resources; regulations; conversion